Factors Influencing Customer Preference in Grocery Retail Industry - Fang, Ze Yeow (2010)
In the past 15 years, majority of researchers conducted in regards to customer satisfaction shows that high satisfaction scores is more often contradicting preference scores and it does not adequately explain the relationship of preference formation versus satisfaction. The predictors generated from the previous researches are therefore, insufficient to help in sustaining the ability to meet customer’s preference. This research identifies the most important elements to formulate the marketing strategies. It is intended to outline the understanding of customer’s perceptions in forming their buying preferences. The aim is to focus on customer’s perceptions in forming their buying preferences. The aim is to focus on customer preference factors that contribute to better business performance in grocery retail industry buy determining the different factors like price, quality, brand and location that forms customer preferences and to recommend a possible customer retention models and suggestion for future marketing strategies. This research used a survey method and interview to conduct research on customer preference. The researcher would like to collect predetermined information from the pool of customers in order to have better insights of influences of the chosen factors in forming buying preferences at consumers’ end. This study can serve as a model for the marketers to understand how customers think, feel, reason, and select between different alternatives (e.g., brands, products, and retailers). Understanding customer preference is the key to enhance the customer loyalty as well as customer relationship management.